Desain Pembelajaran Statistika Menggunakan Konteks Mal di Kelas V - Surya, Apriana; Zulkardi, Zulkardi; Somakim, Somakim (Universitas Hamzanwadi, 2017)
This research is used to help the fifth grade of elementary school statistic easily through mall conteks. It is based on PMRI which is connected to the learning integrative 2013 curriculum. It is used design research type validation study methodology to prove learning theories. This research involved 24 students os Az-Zahrah Palembang in fifth grade level. The students did some activities like (1) making tally (2) drawing and arranging the clothes store (3) cutting and connecting bar chart (4) deciding the clothes stores which is attended in every floor, re arranging the clothes stores every floor, deciding which mall is less and more every floor. And the result shown that by doing same activities above able to help the students in learning statistics.